Is Victorian Poetry Modern?. Issue 1 (30th October 2017) - Guthrie, Bernadette
Abstract: Until recently, the Victorian era has been understood as largely anti‐modern. Much Victorian poetry was simply ignored by critics, who often saw it as regressive. The poets from the period who did garner attention often did so because they seemed to be "ahead of their time." Starting in the 1990s and continuing into the present, literary critics have begun to revisit the question of Victorian poets' relationship to modernity. This scholarship, which often focuses on how poetry from the period was shaped by industrialization and technological innovation, contends that the work of many Victorian poets can be understood as fundamentally modern. This article briefly reviews older scholarship on Victorian poetry's relationship to modernity, surveys more recent critical interventions, and suggests the development of a critical approach to the poetry of the period that would neither collapse the terms "Victorian" and "modern" nor simply set them at odds with one another.